Momentary and personal characteristics predicting maternal fruit and vegetable preparation for children using ecological momentary assessment. (April 2021) - Do, Bridgette; Wang, Shirlene D.; Naya, Christine H.; Dunton, Genevieve F.; Mason, Tyler B.
Abstract: A large body of literature on child-focused research regarding healthy eating within the family context has focused on behavioral management strategies, such as reinforcement, or parental modeling through personal intake or encouragement. However, food preparation behaviors among mothers have been understudied. Also unknown is how maternal food preparation behaviors vary across population subgroups and contexts. The study objective was to elucidate momentary characteristics (i.e., time of day, weekday, and family meals) and personal characteristics (i.e., ethnicity, working status, household characteristics, body mass index, income, and child's age) associated with maternal fruit and vegetable (F/V) preparation through ecological momentary assessment (EMA). 186 mothers (Mage  = 40.81) of children (Mage  = 9.61, 49.5% female) completed six semi-annual waves, each lasting seven days. Mothers completed up to eight EMA surveys a day, which assessed family meals and F/V preparation, and reported personal characteristics through paper questionnaires. Multilevel generalized estimating equations examined the likelihood of F/V preparation. Momentary, within-day characteristics (i.e., occurrence of family meals, weekdays, afternoons) were associated with greater likelihood of mothers' fresh F/V preparation ( p s < 0.05). Additionally, personal characteristics such as non-Hispanic ethnicity, not working full-time, having a child aged six months to five years in the household, and lower child BMI-z were associated with greater fresh F/V preparation among mothers ( p s < 0.05). Findings may inform family-based obesity and nutrition intervention programs by understanding which families and in what contexts mothers are more likely to prepare F/Vs. Highlights: Ecological momentary assessment examined mothers' food preparation behaviors There are inter- and intra-individual differences in maternal food preparation Momentary, within-day factors are related to fruit and vegetable preparation Personal characteristics are related to maternal food preparation Family meal occurrence was associated with fresh fruit and vegetable preparation